Vitamin D Deficiency and the Risk of Preeclampsia and Eclampsia in Bangladesh - Ullah, M. I.; Koch, C. A.; Tamanna, S.; Rouf, S.; Shamsuddin, L. (Hormone and Metabolic Research, 2013)
Maternal vitamin D deficiency has been proposed as a risk factor for preeclampsia, but no significant studies have been conducted to evaluate its relationship with eclampsia. Our goal in this study was to assess the prevalence and potential risk of vitamin D deficiency for both preeclampsia and eclampsia in Bangladesh. Using a case-control design, we measured serum 25(OH)D levels in pregnant women receiving care at the Dhaka Medical College Hospital with preeclampsia (n=33), eclampsia (n=79), and normal pregnancy (controls, n=76). Odds of developing preeclampsia and eclampsia with vitamin D deficiency were calculated using logistic regression analysis. The prevalence of vitamin D insufficiency was very high with more than 3 quarters (78%) of all subjects having a serum 25(OH)D level<30 ng/ml. The mean serum 25(OH)D level was 24.86 ng/ml in controls, 23.96 ng/ml in pre-eclamptic women, and 21.56 ng/ml in eclampsia patients. Comparing to those who had a serum 25(OH)D level of ≥30 ng/ml, the odds ratio (95% CI) of developing preeclampsia and eclampsia in mothers with vitamin D insufficiency were 3.9 (95% CI=1.18–12.87) and 5.14 (95% CI=1.98–13.37), respectively (adjusting for age, BMI and duration of pregnancy). The odds of developing preeclampsia and eclampsia may increase by up to 5-fold in women with vitamin D insufficiency. Since preeclampsia and eclampsia can lead to serious complications for both mother and the offspring, vitamin D may be supplemented during pregnancy in high risk populations to decrease these adverse consequences.
Keywords: vitamin D deficiency; preeclampsia; eclampsia; hypertension